Phantom evaluation of small‐pixel effect in ultra‐high‐resolution photon‐counting CT: Noise texture and high‐contrast spatial resolution - Kyu‐Ho Song; Colin Shan; Gary Xu; Xinhui Duan; Yue Zhang; Kuan Zhang; Liqiang Ren (Journal of Applied Clinical Medical Physics, 2026)
Abstract Background Ultra‐high‐resolution (UHR) photon‐counting CT (PCCT) with small‐pixel detectors improves resolution and noise, but its dependence on diverse imaging conditions remains insufficiently characterized. Purpose To systematically evaluate the small‐pixel effect in UHR PCCT by assessing noise properties and high‐contrast spatial resolution under varying acquisition and reconstruction conditions. Methods Images of an ACR CT accreditation phantom with a body ring simulating a medium‐sized patient were acquired on a clinical PCCT system (NAEOTOM Alpha.Peak, Siemens Healthineers, Germany) using standard‐resolution (STD) and UHR modes. Scans were performed at dose levels ranging from 3 to 24 mGy. Reconstructions included slice thicknesses from 0.2/0.4 to 3.0 mm, convolution kernels from Br36 to Br72, quantum iterative reconstruction both off and at strength levels 1–4, matrix sizes of 512 to 1024, and field‐of‐view (FOV) settings from 210 to 350 mm. Both low‐energy threshold (T3D) and virtual monoenergetic images were evaluated. Image noise was quantified using noise magnitude, noise power spectrum (NPS), and average spatial frequency. High‐contrast spatial resolution was evaluated using the modulation transfer function and visual assessment of resolution patterns. Results Compared with the STD mode, the UHR mode consistently reduced image noise, with the greatest reductions observed at thinner slice thicknesses and with sharper kernels. In contrast, dose level, QIR strength, matrix size, and spectral image type had minimal influence on the relative noise differences between the two modes. NPS analysis further demonstrated lower noise magnitude and, depending on the imaging conditions, a shift of the noise spectrum toward lower spatial frequencies, indicating relative suppression of high‐frequency noise in the UHR mode. High‐contrast spatial resolution was more strongly influenced by imaging sampling conditions, particularly matrix size and FOV, and remained overall comparable between the STD and UHR modes. Conclusions The UHR mode of PCCT consistently achieves lower image noise than the STD mode without compromising high‐contrast spatial resolution. Its greatest benefit is observed in high‐spatial‐resolution imaging protocols employing thin slice thicknesses and sharp reconstruction kernels, whereas the incremental benefit is limited for routine CT imaging. These findings support a task‐based implementation of the UHR mode to optimize protocol selection according to clinical imaging requirements.